Anaesthetic management of an adult patient with Hypertrophic Obstructive Cardiomyopathy and Chronic kidney disease for Minimally Invasive Video Assisted Thoracoscopic Surgery (Indian Journal of Case Reports, 2024)
It is not an uncommon situation to encounter a patient for anaesthesia with multiple co-morbidities. Here we report a successful anaesthetic management of a patient with Hypertrophic Obstructive Cardiomyopathy, Stage IV Chronic Kidney Disease, Chronic Lung Infection, immunosuppressed, posted for minimally invasive video assisted thoracoscopy requiring one lung ventilation. Intraoperative hemodynamic stability was maintained with etomidate, fentanyl, cisatracurium, desflurane & dexmedetomidine with accurate bispectral depth for sedation and precise fluid guidance with transoesophageal echocardiography. The entire anaesthetic conduct was planned to avoid the left ventricular outflow tract obstruction and maintain a steady-state hemodynamic balance. This case report is a learning experience of how close vigilance with appropriate use of monitoring and knowledge about disease per se resulted in uneventful perioperative period.